From one exceptionalism to another: France's strategic relations with the United States and the United Kingdom in the post-Cold War era. Issue 4 (7th June 2017) - Pannier, Alice
ABSTRACT: The failed expedition of Suez in 1956 and France's subsequent strategic 'divorce' from the United Kingdom and the United States lies at the heart of a policy paradigm that has dictated France's defence posture from de Gaulle's presidency to the end of the Cold War. Some crucial features of the Gaullist posture remain today enduring references for French presidents in the definition of France's exceptionalism. While it is so, there have been significant changes since the 1990s when it comes to France's strategic relations with the United States and the United Kingdom. This article demonstrates the extent and mechanisms of this rapprochement by analysing it through three dimensions of policy change: modes of action, institutional commitments and discourses. The article demonstrates the dimensions' mutually reinforcing effects and argues that France's exceptional posture has de facto been reversed.